G PERANCANGAN DAN PROSES MANUFAKTUR MANUAL PRESS KOPI UNTUK USAHA MIKRO KECIL DAN MENENGAH: DESIGN AND MANUFACTURING PROCESS OF MANUAL COFFEE PRESS FOR SMALL AND MEDIUM MICRO ENTERPRISES - Pramudi, Ganjar; Prasetyo, Ari; Harsito, Catur; Akbar, Hammar Ilham; Rovianto, Eki; Sandro, Viki Alex; Hidayat, Rahmat (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
This article explores the manufacturing process of coffee manual presses tailored for small and medium-sized businesses, shedding light on the significance of this brewing method in the modern coffee industry. The coffee manual press, also known as the French press, offers an artisanal approach to coffee brewing, which has gained immense popularity among businesses seeking to provide a unique and memorable coffee experience to their clientele. This discussion delves into the key steps involved in the production of coffee manual presses, including design, material selection, manufacturing techniques, and quality control. Emphasis is placed on the need for precision and consistency in crafting these devices, as they play a pivotal role in the hands of coffee businesses. The article also underlines the importance of understanding the diverse and evolving preferences of coffee enthusiasts, showcasing how the manual press serves as a versatile tool that can unlock a world of flavor and aroma. Small and medium-sized coffee businesses are encouraged to integrate this device into their operations, as it offers an avenue to engage with their customers on a deeper level, create a sense of authenticity, and cater to an expanding range of coffee profiles. In conclusion, this article provides a comprehensive overview of the manufacturing process for coffee manual presses, highlighting their role in elevating the coffee experience for small and medium-sized businesses. By embracing this method, coffee entrepreneurs can brew success, one cup at a time, and create a lasting impact in the competitive coffee market.